If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.45(60) + 0.6x = 0.55(60 + x) Multiply 0.45 * 60 27 + 0.6x = 0.55(60 + x) 27 + 0.6x = (60 * 0.55 + x * 0.55) 27 + 0.6x = (33 + 0.55x) Solving 27 + 0.6x = 33 + 0.55x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.55x' to each side of the equation. 27 + 0.6x + -0.55x = 33 + 0.55x + -0.55x Combine like terms: 0.6x + -0.55x = 0.05x 27 + 0.05x = 33 + 0.55x + -0.55x Combine like terms: 0.55x + -0.55x = 0.00 27 + 0.05x = 33 + 0.00 27 + 0.05x = 33 Add '-27' to each side of the equation. 27 + -27 + 0.05x = 33 + -27 Combine like terms: 27 + -27 = 0 0 + 0.05x = 33 + -27 0.05x = 33 + -27 Combine like terms: 33 + -27 = 6 0.05x = 6 Divide each side by '0.05'. x = 120 Simplifying x = 120
| 7-12s-4s^2=0 | | 8x-12=2x^2 | | x^2-15x-2=0 | | 1-5b-8b^2=0 | | 4x^2+y^2-8x+4y+4=0 | | X(x-3)=x+3 | | 9+6k-8k^2=0 | | 5+7x-6x^2=0 | | 2x^2+7x+14=0 | | 6a^2-5a-2=0 | | 2x^2+7+14=0 | | 6a^2-51-2=0 | | r^2-8r=0 | | 4y^2-y-3=0 | | (2x^3*-7)(6x^3-6)=0 | | 8m^3n^4-22m^5n^6= | | -7x^2-66x-27=0 | | (x-5)(x+1)=4 | | 2+5*x=4x | | 3r^2-2r-5=0 | | -6y-5=7+9y | | 3r^2-24-5=0 | | 10r+8=58 | | 72m^7n+24n= | | 49m^5n^3+28mn^4= | | a^2+13a-68=0 | | 10m^3n^2-25m^2n^3= | | 2s+9s+20=128 | | 7p+9=8p+4 | | 3(x-2)=-2x-16 | | m^3n+9m^2n= | | 4(2x+3u)-3(x-y)= |